Finansowanie ochrony przyrody z budżetu państwa w lasach państwowych w Polsce i w wybranych krajach europejskich – analiza porównawcza - Kaliszewski, Adam (Leśne Prace Badawcze, 2011)
We aim to compare the scope and controls on the public funding of nature conservation by the state in the state forests of Poland and in other selected European countries: Germany (using the regions of Saxony and Bavaria as examples), Austria, and Finland. The study covers various enterprises and economic units, which implement forest management and nature conservation in state-owned forests: Państwowe Gospodarstwo Leśne Lasy Państwowe (Poland), Staatsbetrieb Sachsenforst (Saxony), Bayerische Staatsforsten (Bavaria), Österreichische Bundesforste AG (Austria), and Metsähallitus (Finland). The main sources of information used to make these comparisons included legal documents (laws and regulations) concerning forestry, nature conservation, and public finance, as well as annual economic reports published by the administrative units of the state forests. The study found that in all the selected cases except Poland, reasonable protocols are in place to ensure adequate and long-term allocation of public finances to meet the requirements of nature conservation in state forests. The amount of money transferred to the state forests in Finland, Saxony and Bavaria is defined annually by the parliaments of those countries as a separate expense within the state budgets. In Austria, a suitable level of financing is secured by long-term contracts between the management of Österreichische Bundesforste AG and the public authorities responsible for nature conservation. In Poland, however, the sum allocated annually to nature conservation in the State Forests is designated by the Minister of the Environment from the total pool of money set aside for various tasks related to environmental protection. The article concludes that it is necessary to develop and implement a new procedure for allocating the state budget for nature conservation in Polish State Forests, which would tie the range of protective measures implemented with the size of the grant budgets. In this context it will be essential to explicitly identify in the state budget the finances intended for nature conservation in the State Forests.